Sistem Informasi Laporan Kerja Lapangan Berbasis Web di ULP PLN Helvetia - Muhammad Faruqi; M. Wahyu Ramadhan (Jurnal Media Teknik Elektro dan Komputer, 2024)
Every fieldwork activity report made by the employees of ULP PLN Helvetia is still fairly ineffective because it does not have a good information system. Employees solely generate reports by completing forms provided by their superiors. The impact of this problem lies in the lack of neatness in the data and fieldwork activity reports generated by employees, which naturally leads to ineffective and unstructured work activity reports for the company. To address this issue, we are developing a web-based system for fieldwork activity report information, which simplifies the process for employees and superiors to access neat and structured report data. The implementation of this system has a significant impact on improving efficiency, accuracy, and transparency in managing fieldwork activity reports. The process of recording and managing data becomes faster, more organized, and reduces errors. This study's findings suggest that a web-based system for fieldwork activity report information can streamline data collection for both employees and supervisors. It facilitates the creation of well-structured reports, complete with fieldwork evidence photos, employee work activity entries, and supervisor approval. The system also allows for PDF printing of the report results.